Speech quality for energy criterion in multiplexing - Shah, Asadullah; Shah, Zoya (IIUM Press, 2011)
The energy of speech frames and their usage has been experienced in STDM architectures. Based upon this criterion the design of STOM architecture is experimented and results in terms of extra users and speech quality with 3% frame loss rate is presented in this chapter